The role of vitamin E (tocopherol) supplementation in the prevention of stroke - Bin, Qiong; Hu, Xueying; Cao, Yunfei; Gao, Feng (Thrombosis and Haemostasis, 2011)
It was the objective of this work to systematically evaluate the role of vitamin E supplementation in the prevention of stroke. Eligible studies were identified from Medline, Embase and Cochrane Library. The efficacy data is the relative risk (RR) for the events of stroke. Thirteen randomised controlled trials (RCTs), with 166,282 participants in total, were analysed. The pooled results showed no significant benefit in the vitamin E group with respect to stroke of any type (RR 1.01; 95% confidence interval [CI]: 0.96, 1.07); ischaemic stroke (RR 1.01; 95% CI: 0.94, 1.09), haemorrhagic stroke (RR 1.12; 95% CI: 0.94, 1.33), fatal stroke (RR 0.94; 95% CI: 0.77, 1.14), and non-fatal stroke (RR 0.99; 95% CI: 0.91, 1.08). Administration of vitamin E 300 IU/day or more also gain no benefit (RR 0.99; 95% CI: 0.92, 1.06), as well as vitamin E less than 300 IU (RR 1.05; 95% CI: 0.96, 1.15). Vitamin E supplementation gained benefit of preventing stroke for neither healthy people (0.92; 0.83, 1.03) nor others at high risks in baseline (RR 1.05; 95% CI: 0.98, 1.12). Administration of synthetic vitamin E gain no benefit (RR 1.02; 95% CI: 0.96, 1.09), as well as the natural source vitamin E (RR 0.99; 95% CI: 0.89, 1.09). In conclusion, there is a lack of statistically significant or clinically important benefit of vitamin E supplementation in the prevention of stroke.
Keywords: Vitamin E; stroke; meta-analysis